Hotspoty w bibliotekach – jak bardzo powszechne, jak bardzo potrzebne? - Grygrowski, Dariusz (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
A period, in which getting the access to the Internet at the library required using the computer belonging to the library, and most often wired connected to the network, is ending. More and more libraries are giving users an alternative and more convenient way to use the Internet – access through wifi. All the more, it is possible to use the past tense while talking about the period when one should pay a fee for the access to the Internet in the library. Also, the expression “hotspots in libraries” has recently gained a new meaning. This is because among the items lent by libraries, alongside books and audiovisual materials, there appeared also portable devices called hotspots. They allow users to connect their mobile devices to the Internet practically from the any place – of course also beyond the library. In the article an attempt was made to answer the question of how common it has become in libraries to share the Internet wireless and by what rules it is being realized.